Avaliação do efeito do fluxo e da concentração de ácido acético na corrosão por CO2 dos aços carbono SAE 1020 e 1045 - Monfardini, Warlen Alves (2015)
The CO2corrosion is a big concern in many industries, in particular in the oil and gas exploration field. In this industry, the CO2is in gaseous form and it is hydrated forming H2CO3(carbonic acid). This acid is a weak acid and it can decrease the pH value and increase the corrosion rate. Another factor that has been studied is the presence of acetic acid (HAc) which is present in small concentration (a few mM). Considering the relevance of concentration of acetic acid, presence of CO2and mass transport, this work aim evaluate the flow effect and acid acetic concentration on the CO2corrosion of low carbon steels (SAE 1020 and 1045). Were performed the potentiodynamic polarization by a RDE geometry in solution with 3 % NaCl, saturated by CO2(1 atm), andsmall concentration of HAc (0, 300, 1000, 2000 ppm). Through the polarization curves was possible to observe a significant influence of the flow and concentration of HAc on the corrosion parameters like Ecorr, Icorr, Ilim, ba, bcand Ru. This behavior evidence a complex interaction between anodic and cathodic reactions on the corrosion process in presence of HAc. After each testing, the superficial surface wasobserved by optical microscopy and scanning electron microscopy (SEM). Was observed pitting attack in practically all conditions